The evolution of the fruit sector in Romania between 2010-2016 - Petruța Antoneta Turek-Rahoveanu; Daniela Nicoleta Bădan (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 8th Edition of the International Symposium, November 2017, Bucharest, 2017)
In this article we analyze the current state of the fruit sector in Romania as well as the evolution of this sector between 2010-2016. Considering the importance of fruit consumption, this article aims to analyze the evolution of the surfaces, productions and average prices for the main inland fruits. Due to the decrease of the orchard surfaces and tree farms we can see variations in the productiveness per hectare, which leads to a high degree of imbalance in procurement. Sustaining the fruit sector is one of the primary directions of PNDR 2014-2020 through the Food-Growing Subprogram.
Keywords: Q13; L11; 330; areas; production; productiveness